2020
DOI: 10.1371/journal.pone.0235416
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a new terpene synthase from Plectranthus amboinicus

Abstract: Plectranthus amboinicus (Lour.) Spreng is an aromatic medicinal herb known for its therapeutic and nutritional properties attributed by the presence of monoterpene and sesquiterpene compounds. Up until now, research on terpenoid biosynthesis has focused on a few mint species with economic importance such as thyme and oregano, yet the terpene synthases responsible for monoterpene production in P. amboinicus have not been described. Here we report the isolation, heterologous expression and functional characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 78 publications
3
17
0
Order By: Relevance
“…The P. amboinicus linalool/nerolidol synthase (designated as PamTps1 ) (GenBank accession no: MK050501) was previously isolated and functionally characterized by Ashaari et al 15 . Enzyme assay was conducted in a 100 µl reaction containing assay buffer (10 mM Tris–HCl, pH 7.5, 10% (v/v) glycerol, 1 mM DTT, 0.1 mM NaWO 4 , 0.05 mM NaF), 10 mM MgCl 2 and 3–5 µg of purified protein.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The P. amboinicus linalool/nerolidol synthase (designated as PamTps1 ) (GenBank accession no: MK050501) was previously isolated and functionally characterized by Ashaari et al 15 . Enzyme assay was conducted in a 100 µl reaction containing assay buffer (10 mM Tris–HCl, pH 7.5, 10% (v/v) glycerol, 1 mM DTT, 0.1 mM NaWO 4 , 0.05 mM NaF), 10 mM MgCl 2 and 3–5 µg of purified protein.…”
Section: Methodsmentioning
confidence: 99%
“…These compounds are widely used as fragrance materials in cosmetic products including perfumes, lotions and shampoos, and in non-cosmetic products such as detergents and cleansers. Isolation and characterization of this enzyme were reported from Plectranthus amboinicus 15 , Rosa chinensis 14 , Hedychium coronarium 23 , Vitis vinifera 24 and Antirrhinum majus 13 which showed that this type of bifunctional enzyme is widespread across multiple plant species. The multi-substrate activity may confer advantages on plants to adapt rapidly in response to changes in the substrate profile under perturbation of metabolism in stressed plants, as well as under certain developmental changes without compromising their central metabolism 12 .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Plectranthus amboinicus was obtained from purchased plants that were maintained at the BioTech2 Building, Faculty of Biotechnology and Biomolecular Sciences, Universiti Putra Malaysia (3 • 00 26.4" N 101 • 42 19.3" E). Authentication of the plant was conducted by Dr Shamsul Khamis and deposited as a herbarium specimen with the voucher number UKMB40411 at the Universiti Kebangsaan Malaysia (UKM), Bangi, Selangor, Malaysia [12].…”
Section: Plant Materialsmentioning
confidence: 99%